2005
DOI: 10.1016/j.cardiores.2005.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling studies of aging in cardiac and skeletal muscles

Abstract: To examine transcriptional alterations associated with aging in skeletal muscle and the heart, we and others have used DNA microarrays to compare the gene expression profile of young and old animals. Aging results in a differential gene expression pattern specific to each tissue, and most alterations can be completely or partially prevented by caloric restriction (CR) in both heart and skeletal muscle. Transcriptional patterns of tissues from calorie-restricted animals suggests that CR retards the aging proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 69 publications
(71 reference statements)
2
65
0
3
Order By: Relevance
“…The aged heart changes its metabolism to glucose consumption, with repressed fatty acid use. 36 Perhaps an increase in the availability of fatty acids for storage promotes commitment of stem cells toward the adipocyte lineage. It is not clear whether met- Reduced TGF-␤1-dependent Smad3 activation in fibroblasts derived from aged animals.…”
Section: Rescue Of Defective Function Requires Ampk Activationmentioning
confidence: 99%
“…The aged heart changes its metabolism to glucose consumption, with repressed fatty acid use. 36 Perhaps an increase in the availability of fatty acids for storage promotes commitment of stem cells toward the adipocyte lineage. It is not clear whether met- Reduced TGF-␤1-dependent Smad3 activation in fibroblasts derived from aged animals.…”
Section: Rescue Of Defective Function Requires Ampk Activationmentioning
confidence: 99%
“…Involvement of cell cycle regulatory mechanisms in senescence has been shown in proliferating cells. However, few studies of senescence in cardiomyocytes are reported, because cardiomyocyte is terminally differentiated cell (Torella et al ., 2004;Park & Prolla, 2005). It is important to determine whether cell cycle regulators play key roles in senescence of cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, culturing HeLa cells with serum from CR rats induces expression of mitochondrial genes, and these changes are associated with an increased number of mitochondria per cell compared with cells cultured in serum from ad libitum fed rats (5). Certainly, CR induces expression of genes involved in mitochondrial energy metabolism in many tissues, including skeletal muscle, heart, and white adipose tissue (4,(6)(7)(8). The skeletal muscle response to CR is particularly interesting for two reasons.…”
mentioning
confidence: 99%